Implementasi Prinsip-Prinsip Evaluasi Pembelajaran Pada Mata Pelajaran Pendidikan Agama Islam - Marzuki, Ismail (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
In the learning process, a teacher's job is not only to be an educator, or even just to convey learning material to students, but a teacher must also act as an evaluator. The role of education as an evaluator in the learning process must and must use the principles of learning evaluation, namely the principles of continuity, comprehensiveness, objectivity and practicality. Through the implementation of the principles of learning evaluation, a quality learning process and maximum learning outcomes in achieving learning goals are obtained. The aim of implementing learning evaluation is to obtain evidentiary data that shows the level of student ability and success in achieving learning objectives. Apart from that, it can also be used by teachers and educational supervisors to measure or assess the effectiveness of teaching experiences, learning activities and learning methods used in the learning process. Keywords: learning process, principles and learning evaluation.